The Influence of Transformational, Servant, and Authentic Leadership on Driving Innovation and Creativity in Organizations - Purwaningrum, Ike; Mujahid, Mujahid; Sukmarini, Andi Vita (Scieclouds Publishing, 2024)
Imagination and creativity play significant roles in sustaining the competitive edge in the current fluid business environment. This paper explores leadership and creativity, particularly change, transactional and servant and authentic leadership styles. Descriptive research was employed and questionnaires were administered on 250 respondents from different organizations and administrative regression analysis used. The personal factors established indicate that among all the leadership styles, transformational leadership generates high positive influence on creativity and innovation as it inspires employees to try out new ideas that can help overcome old structures. There is also a huge positive impact from servant and authentic leadership which promote support, ethical standards and information sharing. On the other hand, transactional leadership arranged in the aspect of goal setting and rewards gives a small impact in encouraging creativity as it preserves the current system. The present research fulfills the silences of the existing literature by offering insights into the impact of differentforms of leadership on innovation and creativity While doing so, the study emphasized the need to adopt leadership strategies that foster risk taking, collaboration and decentralised decision making among employees. These findings imply that someone who wants to enhance innovation in an organization should support three forms of leadership: transformational, servant, and authentic leadership.